2022
DOI: 10.1007/s11356-022-18686-1
|View full text |Cite
|
Sign up to set email alerts
|

Decarbonization: examining the role of environmental innovation versus renewable energy use

Abstract: Climate change resulting from a rapid increase in greenhouse gas (GHG) emissions is adversely affecting humanity. If the GHG emission continues to rise at the current pace, humanity will face severe consequences and reverse all the progress made. This paper, therefore, uses relevant data from 14 developing countries in Asia from 1990 to 2018 to examine the potential impact of environmental innovation on CO2 emissions by controlling globalization, urbanization, and economic growth. The number of environmental-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 84 publications
0
13
1
Order By: Relevance
“…Hence, technological advancement plays important role in decreasing environmental footprints. Sahoo et al (2022) uses appropriate data from 14 developing Asian countries for the period of 1990 to 2018 and determined that environmental technology innovations play an inadequate role in reducing emissions and in the presence of suitable economic developmental investment. Abid et al (2021) also establish that renewable energy consumption and technology facilitated a reduction in CO 2 emissions, in the case of Pakistan.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hence, technological advancement plays important role in decreasing environmental footprints. Sahoo et al (2022) uses appropriate data from 14 developing Asian countries for the period of 1990 to 2018 and determined that environmental technology innovations play an inadequate role in reducing emissions and in the presence of suitable economic developmental investment. Abid et al (2021) also establish that renewable energy consumption and technology facilitated a reduction in CO 2 emissions, in the case of Pakistan.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to the Environmental Kuznets Curve hypothesis, economic growth leads to environmental degradation, and after a certain level of economic development, the marginal utilities of a better environment increase, and countries will start investing in clean technology (Selden and Song 1994;Zhu et al 2016;Narayan and Narayan 2010). However, the literature differs in terms of the validity of the Environmental Kuznets Curve hypothesis (Sahoo et al 2022).…”
Section: Way Forward Environmental Kuznets Curve Hypothesismentioning
confidence: 99%
“…The literature has also suggested that the increase in deployment of environmentally friendly technology leads to a decline in GHG emissions (Sahoo et al 2022;Bhowmik et al 2022). Therefore, investment and scaling of green technology could significantly contribute to the reduction of GHG emissions.…”
Section: Technologymentioning
confidence: 99%
“…Over the last century, the emergency of negative environmental issues, such as climate change, global warming, greenhouse gas emissions, and overall environmental degradation—often ensuing from uncontrolled economic and social progress—makes the necessity to identify suitable deterrents able to hinder these negative impacts (Sahoo et al, 2022). It is significant for companies to earnestly take into account these environmental concerns, especially in front of a broader expansion of environmental policy involving green management practices (i.e., responsible use of resources, innovation, emissions reduction, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the present study explores environmental innovation and board gender diversity as drivers to underplay firm's environmental issues and, at the same time, reduce financial risks. On the one hand, environmental innovation represents a chance to strongly mitigate global environmental degradation (Farza et al, 2022; Sahoo et al, 2022); on the other hand, board structure might boost to achieve such a goal (Gurol & Lagasio, 2022; Khatri, 2023). Our contribution provides intriguing food for thought to rethinking the business management practices and board of directors (BDs) composition, with the aim to extend gender inclusivity and environmental concern into firm's mindset.…”
Section: Introductionmentioning
confidence: 99%